A Study of Equitisation in Vietnam - Tran, Ngoc Bich (2008)
Most of studies on privatisation are conduxted in developed countries in the west or transitional economies in Central and Eastern Europe. Hence, little is known about equitisation in Vietnam though it started in the same decade with other transitional economies and had gained impressive achievements. In addition, studies conducted in Vietnam are most likely in Vietnamese thus being circulated among only a small number of interested readers. In the area of globalisation, this study is conducted in English with hope to contribute its humble part to studies about equitisation in Vietnam which covers wider readership. It captures the picture of privatisation in certain transitional economies for comparison purposes with the equitisation in Vietnam. This research instrument is modified from the questionnaires from Thai (2006), Truong (2006) and other relevant studies on this topic. The study has two main objectives such as comprehending the equitisation process in Vietnam abd relating impacts. Findings reveal about the Factors Affecting the Duration of Equitisation Process, Factors Influencing the Choice of Firms to Equitise, Drivers Equitisation Programme and Impacts of equitisation in Vietnam.